The Role Of The Principal As A Leader In Disciplining Elementary School Teacher - kardianty, Arnen; Siti Quratul ain (International Journal of Elementary Education, 2022)
Discipline is one of the factors that can indicate the quality of one's performance. It's just that the reality on the ground shows that the level of teacher discipline is still relatively low, so it requires serious attention from the school principal. The purpose of this study is to find out the role of the principal as a leader in disciplining teachers. This research belongs to the type of qualitative descriptive research with the research subject being a school principal in a public elementary school. Data collection in the research was carried out using observation, interview and documentation methods. The data studied were sourced from primary data in the form of school principals and teachers, and secondary data in the form of research results supporting documents. The instrument used in this study was a questionnaire sheet with 3 indicators and 6 sub-indicators. The data obtained in the study were then analyzed using descriptive qualitative analysis techniques and linking the research results with the results of previous studies. The results of the research analysis show that the role of the principal as a leader in disciplining teachers has been carried out by the principal well, the principal has disciplined the teacher by means of the principal as a giver of direction, the principal as an agent of change, the principal as a coach. There are three obstacles experienced by the principal, namely the role of the principal as a giver of direction, the principal as an agent of change and the principal as a coach.